Scalable reaction network modeling with automatic validation of consistency in Event-B - Sanwal Usman; Hoang Thai Son; Petre Luigia; Petre Ion (NATURE PORTFOLIO, 2022)
Constructing a large biological model is a difficult, error-prone process. Small errors in writing a part of the model cascade to the system level and their sources are difficult to trace back. In this paper we extend a recent approach based on Event-B, a state-based formal method with refinement as its central ingredient, allowing us to validate for model consistency step-by-step in an automated way. We demonstrate this approach on a model of the heat shock response in eukaryotes and its scalability on a model of the ErbB signaling pathway. All consistency properties of the model were proved automatically with computer support.